(untitled) (Zaporizhzhia Historical Review, 2021)
The article is based on the archival source materials, which are taken from the town’s records stored in the State Archive in Zamość. The author presents the economic and social image of Zamość during the Polish and Soviet War in 1920.The main description in the article concerns the attitude of the inhabitants of Zamość in the time of the direct military danger. The depict situation took place at the last days of August during the attack of the 1st Horse Army of Siemion Budionny on Zamość. The substantive documents of the described phenomena and events exemplify the not well known biographical context of the then defence commander of Zamość – colonel Marek Bezruczko from the People’s Republic of Ukraine.